Minicell‐based fungal RNAi delivery for sustainable crop protection. Issue 4 (24th February 2021) - Islam, Md Tabibul; Davis, Zachery; Chen, Lisa; Englaender, Jacob; Zomorodi, Sepehr; Frank, Joseph; Bartlett, Kira; Somers, Elisabeth; Carballo, Sergio M.; Kester, Mark; Shakeel, Ameer; Pourtaheri, Payam; et al.
Summary: Spray‐induced gene silencing (SIGS) using topical dsRNA applications has risen as a promising, target‐specific, and environmentally friendly disease management strategy against phytopathogenic fungi. However, dsRNA stability, efficacy, and scalability are still the main constraints facing SIGS broader application. Here we show that Escherichia coli ‐derived anucleated minicells can be utilized as a cost‐effective, scalable platform for dsRNA production and encapsulation. We demonstrated that minicell‐encapsulated dsRNA (ME‐dsRNA) was shielded from RNase degradation and stabilized on strawberry surfaces, allowing dsRNA persistence in field‐like conditions. ME‐dsRNAs targeting chitin synthase class III ( Chs3a,   Chs3b ) and DICER‐like proteins ( DCL1  and  DCL2 ) genes of  Botryotinia fuckeliana selectively knocked‐down the target genes and led to significant fungal growth inhibition  in vitro . We also observed a compensatory relationship between DCL1 and DCL2 gene transcripts, where the silencing of one gene upregulated the expression of the other. Contrary to naked‐dsRNAs, ME‐dsRNAs halted disease progression in strawberries for 12 days under greenhouse conditions. These results elucidate the potential of ME‐dsRNAs to enable the commercial application of RNAi‐based, species‐specific biocontrols comparable in efficacy to conventional synthetics. ME‐dsRNAs offer a platform that can readily be translated to large‐scale production and deployed in open‐field applications to control grey mould in strawberries. Abstract : Spray‐induced gene silencing (SIGS) using topical dsRNA applications has risen as a promising, target‐specific, and environmentally‐friendly disease management strategy against phytopathogenic fungi. We demonstrated that minicell‐encapsulated dsRNA (ME‐dsRNA) halted gray mold disease progression in strawberries. ME‐dsRNAs offer a platform that can readily be translated to large‐scale production and deployed in open‐field applications to control gray mold in strawberries.